Spatiotemporal Molecular Approach of in utero Electroporation to Functionally Decipher Endophenotypes in Neurodevelopmental Disorders - Kolk, Sharon M.; De Mooij - Van Malsen, Annetrude J.; Martens, Gerard J. (Frontiers in Molecular Neuroscience, 2011)
We have only just begun to decipher the complexity of our brain including its maturation. Correct brain development and communication among brain areas are crucial for proper cognitive behavior. Brain area-specific genes expressed within a particular time window direct neurodevelopmental events such as proliferation, migration, axon guidance, dendritic arborization and synaptogenesis. These genes can pose as susceptibility factors in neurodevelopmental disorders eventually resulting in area-specific cognitive deficits. Therefore, in utero electroporation-mediated gene transfer can aid in creating valuable animal models in which the regionality and time of expression can be restricted for the targeted gene(s). Moreover, through the use of cell-type specific molecular constructs, expression can be altered in a particular neuronal subset within a distinct area such that we are now able to causally link the function of that gene in that brain region to the etiology of the disorder. Thus, in utero electroporation-mediated gene transfer is an attractive molecular technique to spatiotemporally address the developmental aspects of gene function in relation to neurodevelopmental disorder-associated endophenotypes.